Impact of surgical intensive care unit interdisciplinary rounds on interprofessional collaboration and quality of care: Mixed qualitative–quantitative study. (February 2018) - Urisman, Tatiana; Garcia, Alberto; Harris, Hobart W.
Highlights: Interprofessional collaboration is a key component of effective patient care delivery in the critical care setting. Interdisciplinary surgical ICU rounds with formal participation of bedside nurses improve communication and collaboration between health care providers. A trend for reduced adverse events (falls and self-extubations) following the introduction of surgical ICU interdisciplinary rounds observed in this study supports the argument that enhanced interprofessional collaboration improves quality of patient care. Abstract: Background: Interprofessional collaboration is a key requirement for safe and effective care delivery in the critical care setting. To promote collaboration between care providers, intensive care unit interdisciplinary rounds have been introduced by multiple institutions and subsequent subjective improvements in interprofessional collaboration have been reported. However, only limited data are currently available regarding the impact of these rounds on objective patient care outcomes. Objectives: The study had two main goals: (i) to evaluate the impact of introducing an interdisciplinary rounding format that formalised the participation of nurses in rounds on the effectiveness of interprofessional collaboration, specifically between nurses and physicians; and (ii) to evaluate a possible impact of adopting these rounds on measurable patient care outcomes. Methods: General surgery rounds were introduced in our 32-bed medical-surgical intensive care unit. The impact of the rounds on the quality of collaboration was measured using anonymous web-based surveys of nurses and surgeons. Rates of falls and self-extubations (adverse events) were compared during five month pre- and post-intervention periods (August 2014–Jun 2015). Results: Both nurses and physicians reported subjective improvement in collaboration following the introduction of interdisciplinary rounds. Additionally, a decline in both rates of falls and self-extubations was observed in the post-intervention period; however, due to the rarity of these events, neither trend reached statistical significance. Conclusions: Interdisciplinary rounds provide an attractive model for improving interprofessional collaboration in critical care. Our findings add support to the growing evidence that interdisciplinary rounds improve collaboration and have a positive impact on the quality of patient care delivery.